CAPS Psychology and the Empirical Adequacy of Aristotelian Virtue Ethics - Papish, Laura (Ethical theory and moral practice, 2017)
For the past decade and a half, Aristotelians have tried to counter the following criticism articulated by John Doris: if we look at personality and social psychology research, we must conclude that we generally neither have, nor have the capacity to develop, character traits of the kind envisioned by Aristotle and his followers. Some defenses of Aristotelian virtue ethics proceed by trying to insulate it from this challenge, while others have tried to dissipate the force of Doris's critique by showing how virtue ethics and recent findings in personality psychology share surprisingly extensive common ground. For example, in their 2009 books, Daniel Russell and Nancy Snow both argue that the empirical research regarding character complements - not undermines - virtue ethics. Specifically, each argues that the situationally sensitive Cognitive-Affective Personality System (CAPS) developed by Walter Mischel and Yuichi Shoda can be integrated into a virtue ethical moral philosophy and theory of character. In this paper, I raise several objections to their attempts to use the CAPS model to rehabilitate Aristotelian virtue ethics and argue that, as a result, this model has not been shown to have the promise Snow and Russell allege it has.